Perceived barriers to physical activity among women with arthritis - Hillard, Sara A. (Kansas State University, 2008)
Arthritis is one of the most prevalent and debilitating chronic health conditions for Americans. As no cure exists for arthritis, one emphasis of treatment focuses on the self-management of the disease through regular physical activity. Despite the well known health benefits, low physical activity rates exist among people with arthritis, particularly women. Research needs to focus on what influences decisions to participate in physical activity, one such influence is barriers. The purpose of the study was to examine the relationships among perceived barrier presence and perceived barrier limitation of 25 general and 16 arthritis-specific barriers and moderate physical activity. Participants were 279 women (M = 48.57years) with arthritis who completed a web-based survey. A hierarchical multiple regression to predict moderate physical activity was significant (p < .001). General barrier limitation contributed the most to predicting total moderate physical activity participation. Education, body mass index, general barrier presence, arthritis-specific barrier presence, and arthritis-specific barrier limitations were also significant independent predictors. Findings suggest that the more general and arthritis-specific barriers identified (barrier presence) and higher extent of limitation (barrier limitation) was associated with lower levels of participation in physical activity. Future research would benefit from including a measurement of frequency of perceived barriers to better understand the impact of barriers to physical activity. A greater understanding of general and arthritis-specific barriers to physical activity may be used as a basis for targeted interventions to help women with arthritis participate in physical activity.
Keywords: Arthritis; Physical activity; Barriers; Health Sciences, General (0566)